Podbor tenzogeometriceskich i castotnych charakteristik lyž v sootvetstvii s reologiceskimi charakteristikami snežnoj trass - Ryazanov, A. G.; Ryazanov, A. A.; Dogov, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
This article presents an influence study of the snow track rheological characteristics for a wide range on ski glide. In addition, substantiates the corresponding optimal strain-gauge and frequency characteristics is given. An experimental verification of the obtained results of theoretical studies has been carried out. The high efficiency of selection of strain-gauge and frequency characteristics of skis is shown, taking into account the rheological characteristics of the snow track.